2015
DOI: 10.3109/10717544.2015.1031295
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of baicalein and doxorubicin by hyaluronic acid decorated nanostructured lipid carriers for breast cancer therapy

Abstract: Purpose: Combination anticancer therapy is promising to generate synergistic anticancer effects, to maximize the treatment effect and to overcome multi-drug resistance. Nanostructured lipid carriers (NLCs), composed of solid and liquid lipids, and surfactants are potentially good colloidal drug carriers. The aim of this study is to construct a hyaluronic acid (HA) decorated NLCs as nanocarriers for co-delivery baicalein (BCL) and doxorubicin (DOX). Methods: BCL-and DOX-loaded NLCs (BCL/DOX-NLCs) were prepared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…[42][43][44][45] Nanocarriers using lipids to load drugs form a carrier system with a number of desirable features, including a low toxicity, a biodegradable particulate matrix, nontoxic degradation products, a high capacity to incorporate lipophilic and hydrophilic drugs, a controlled release of the incorporated drug, and easy scale-up at low cost. 46 For this purpose, different types of lipid carriers, including lipid-drug conjugates, SLNs, and NLCs, have been developed. NLCs represent a new generation of lipid nanoparticles, which are developed through the combination of advantages from different nanocarriers, including liposomes and SLN systems.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Nanocarriers using lipids to load drugs form a carrier system with a number of desirable features, including a low toxicity, a biodegradable particulate matrix, nontoxic degradation products, a high capacity to incorporate lipophilic and hydrophilic drugs, a controlled release of the incorporated drug, and easy scale-up at low cost. 46 For this purpose, different types of lipid carriers, including lipid-drug conjugates, SLNs, and NLCs, have been developed. NLCs represent a new generation of lipid nanoparticles, which are developed through the combination of advantages from different nanocarriers, including liposomes and SLN systems.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, hyaluronic acid (HA), a non-toxic, biocompatible and biodegradable polysaccharide, has gained intense attention due to its potential as drug delivery carrier (Almeida et al, 2014;Laffleur et al, 2014;Liu et al, 2015). Many studies have reported that HA receptors in human body played important biological roles, such as endocytosis, degradation and signal transduction (Oh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-based nanoparticles can be considered as a versatile tool with a high potential of applications, including a high capacity to incorporate lipophilic and hydrophilic drugs, a biocompatible and biodegradable matrix and well-established safety profiles (Esposito et al, 2015;Liu et al, 2015). They combine advantages of colloidal drug carrier systems such as emulsions, liposomes and polymeric nanoparticles.…”
Section: Introductionmentioning
confidence: 99%